Note On An Error in Hazlitt’s Economics in One Lesson - Block, Walter (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2020)
Economics in One Lesson is the best introduction to economics ever written. It has enticed, educated, and inspired multitudes of people to embrace the teachings of the dismal science. To the extent that if there is any understanding of economics by the general public, it is due more to this book than to any other. Yet, I have uncovered one error in it, which I attempt to rectify, offering a very slightly improvement to a priceless book on economics.